Synthesis of Novel 6-(1H-pyrazol-4-yl)-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles as Potential Antimicrobial Agents - Pundeer, Rashmi; Ranjan, Pooja; Prakash, Richa; Joshi, Radhika (Letters in Organic Chemistry, 2018)
Background: Triazolothiadiazoles are molecules of great synthetic and pharmacological significance. They are associated with significant antimicrobial, antifungal, antibacterial, antihelmintic and anti-inflammatory activities. Method: The condensation of 5-alkyl-4-amino-3-mercapto-4H-1,2,4-triazoles with 3-aryl-1- phenylpyrazole-4-carboxylic acids was carried out in the presence of phosphoryl chloride and the resulting products were tested in vitro for their antibacterial potential against Bacillus subtilis (gram positive), Staphylococcus aureus (gram positive), Escherichia coli (gram negative) and Pseudomonas aeruginosa (gram negative) and further antifungal properties against Candida albicans, and Saccharomyces cervisiae. Results: A new series of 3-alkyl-6-(3-aryl-1-phenyl-1H-pyrazol-4-yl)-[1,2,4]triazolo[3,4-b][1,3,4] thiadiazoles has been synthesized by the reaction mentioned above. One specific compound, 6-(3-(4- fluorophenyl)-1-phenyl-1H-pyrazol-4-yl)-3-methyl-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazole displayed an excellent antifungal activity against Candida albicans with a MIC value of 8 μg/ml, which is actually even better than the standard drug Amphoptericin B (MIC 10 μg/ml). Conclusion: An expeditious synthesis of several new 3-alkyl-6-(3-aryl-1-phenyl-1H-pyrazol-4-yl)- [1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles in 77-89 % yield could be performed from readily accessible starting materials, 5-alkyl-4-amino-3-mercapto-4H-1,2,4-triazoles and 3-aryl-1-phenylpyrazole-4- carboxylic acids. Most of the resulting compounds showed moderate to good in vitro activity against Gram-positive bacteria. The title compounds seem to be more active against fungi than bacteria.
Keywords: 3-Alkyl-6-(3-aryl-1-phenyl-1H-pyrazol-4-yl)-[1